Analisis Pemahaman Konsep Matematika Ditinjau dari Minat Belajar Siswa Kelas XI IIS SMA PGRI 3 Padang - Zesni Syiapuri; Yulia Haryono; Ratulani Juwita (STKIP PGRI Sumatera Barat, 2022)
This study aims to describe the understanding of mathematical concepts in terms of students' interest in learning transformation material. This research method is a descriptive analysis method with a qualitative approach. The subjects of this study were students of class XI IIS SMA PGRI 3 Padang in the 2021/2022 academic year. The sampling technique is based on the level of understanding of the concept and learning interests of students. The instruments used to collect data are in the form of tests, interest in learning questionnaires, and interviews. The results showed that students with high learning interest with high and moderate conceptual understanding were able to fulfill the indicators for restating a concept and applying concepts or algorithms to problem solve. Students with moderate learning interest with high and low concept understanding are less able to fulfill the indicators for restating a concept. Students with low learning interest with moderate and low concept understanding are not able to meet the indicators in restating a concept, applying concepts or algorithms in problem-solving, and presenting concepts in the form of mathematical representations. Keywords: Analysis Of Concept Understanding, Learning Interest